Associations Between Academic Stress, Mental Distress, Academic Self-Disclosure to Parents and School Engagement in Hong Kong - Chyu, Esther Pui Yung; Chen, Ji-Kang (Frontiers in Psychiatry, 2022)
Numerous studies have indicated that academic stress is associated with various detrimental personal physical and emotional outcomes; however, relatively few studies have explored how academic stress affects adolescents’ interactions with their significant others in families and schools, which are two important social systems for school-age adolescents. In addition, there are also few studies examining how academic stress influences adolescents’ self-disclosure to parents and school engagement in East Asian districts particularly in Hong Kong, where the level of academic stress among adolescents is high. This study examines how academic stress affects mental distress, academic self-disclosure to parents and school engagement and explores gender differences in the risk for the outcomes of academic stress. One thousand and eight hundred and four students from eight secondary schools in Hong Kong participated in this study. The results indicate that academic stress has a significant association with all three outcomes, but the correlation with school engagement is positive, which is contrary to the findings of most previous studies, the possible reasons for such positive association are discussed. In addition, the model can be applied to both genders, but females are more susceptible to the detrimental outcomes of academic stress by suffering a higher level of mental distress. This study suggests that academic stress should be an important entry point to tackle adolescents’ mental distress while interventions should be targeted at females who are experiencing a higher level of mental distress. In addition, in view of the significant associations between academic stress and self-disclosure to parents, as well as between academic stress and school engagement, suggestions are provided to families and schools on how to proactively provide support to those students who are experiencing academic stress.